Principles of using esmolol in the practice of anesthesiologists and intensive care physicians (Perioperaciina Medicina, 2021)
Prevention and reduction of cardiac risk remains an important issue in anesthesiology and intensive care. There is a successful clinical experience in the use of esmolol for the correction of hemodynamic and ischemic disorders in acute coronary syndrome, in the perioperative period with excessive activation of the sympathoadrenal system. A large number of works are devoted to the use of esmolol as a drug that prevents hemodynamic changes due to tracheal intubation. The aim of the study was to evaluate the use of esmolol and dexmedetomidine as intravenous adjuvants in general analgesia during thyroidectomy in patients with thyrotoxicosis. The use of esmolol (Biblock) and dexmedetomidine in anesthesia for thyroidectomy, suppresses the hemodynamic response caused by surgical stress. Both adjuvants stabilize oxygen consumption and maintain a stable metabolism. Both drugs are quite effective as intravenous adjuvants in general analgesia for thyroidectomy in patients with thyrotoxicosis. They are the drugs of choice and can be recommended in practical anesthesiology.
Keywords: anesthesiology and intensive care; selective beta-1-blocker esmolol